Ixodes (Pholeoixodes) hexagonus, an efficient vector of Borrelia burgdorferi in the laboratory - Gern, Lise; Toutoungi, L. N.; Hu, Chang Min; Aeschlimann, André (My University, 1991)
Borrelia burgdorferi Johnson et al. was first isolated from the midgut of Ixodes dammini Spielman et al. in the U.S.A. and from the midgut of Lricinus (L.) in Europe. I.ricinus was considered to be the only tick vector of this borrelia, in Europe, until I.hexagonus Leach, the hedgehog tick, was found to harbour spirochaetes. This paper reports an evaluation of the vector competence of I. hexagonus for the spirochaete B. burgdorferi. Transovarial and trans-stadial survival were demonstrated and the spirochaete was transmitted to laboratory mice via the bites of trans-stadially infected I.hexagonus females.
Keywords: Ixodes hexagonus; hedgehog ticks; Borrelia burgdorferi; Lyme disease; vector competence